2015
DOI: 10.1039/c5fo00405e
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of geraniol ameliorates acute experimental murine colitis by inhibiting pro-inflammatory cytokines and NF-κB signaling

Abstract: Ulcerative colitis is associated with a considerable reduction in the quality of life of patients. The use of phyto-ingredients is becoming an increasingly attractive approach for the management of colitis. Geraniol is a monoterpene with anti-inflammatory and antioxidative properties. In this study, we investigated the therapeutic potential of geraniol as a complementary and alternative medicine against dextran sulphate sodium (DSS)-induced ulcerative colitis in mice. Disease activity indices (DAI) comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…It also modulated the expression of caspase-3, intercellular adhesion molecule-1, and glycogen synthase kinase-3β as well as the β-catenin, p38 MAPK, NF-κB, and peroxisome proliferator-activated receptor γ signaling pathways in the same way as did sulfasalazine [92]. In addition, treatment with geraniol reversed DSS-induced inflammation and oxidative alterations [93]. However, no study has investigated the effect of citronellal on colitis.…”
Section: Family Rosaceaementioning
confidence: 94%
“…It also modulated the expression of caspase-3, intercellular adhesion molecule-1, and glycogen synthase kinase-3β as well as the β-catenin, p38 MAPK, NF-κB, and peroxisome proliferator-activated receptor γ signaling pathways in the same way as did sulfasalazine [92]. In addition, treatment with geraniol reversed DSS-induced inflammation and oxidative alterations [93]. However, no study has investigated the effect of citronellal on colitis.…”
Section: Family Rosaceaementioning
confidence: 94%
“…Pretreatment with GE showed an inhibitory effect on the amount of proinflammatory cytokines and the activity of myeloperoxidase in colon tissue. GE downregulated the expression of downstream target proinflammatory enzymes but upregulated antioxidant molecules: GSH and superoxide dismutase activity were suppressed and LPO and nitrites increases were prevented [36].…”
Section: Colon Cancermentioning
confidence: 99%
“…The present review also suggested that higher oral doses and enema administration of Ge-OH strongly reduces dysbiosis and systemic inflammation in dextran sulfate sodium-treated mice by significantly decreasing plasma levels of IL-1β, IL-17, IFN-γ, and TNF-α (De Fazio et al, 2016). Also, oral administration of geraniol at doses of 50 and 100 mg/kg body weight ameliorates acute experimental murine colitis by inhibiting the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 and NF-κB signaling (Medicherla et al, 2015).…”
Section: <Insert Figure 3>mentioning
confidence: 99%